2010
DOI: 10.1002/jbmr.64
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological skeletons support a northwest European origin for Paget's disease of bone

Abstract: The strong genetic component in the etiology of Paget's disease of bone (PDB), together with marked geographic variation in its prevalence, with high frequencies in British populations, has led some to suggest that the disease originated in Britain and spread around the world in recent times by the migration and admixture of British populations. This study aims to investigate this hypothesis by studying the world geographic distribution of PDB cases identified in ancient skeletons excavated from archaeological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 10 publications
1
18
0
5
Order By: Relevance
“…Conversely, PDB is rare in Scandinavia, the Indian subcontinent, China, Japan, and other countries in the Far East [9]. These observations are consistent with recent archeological studies that have indicated that PDB most probably originated in Britain and spread to other parts of the world as the result of migration and genetic admixture [10]. Genetic studies in patients with the P392L mutation of SQSTM1 (the most common causal mutation of PDB, see later) also support this hypothesis in demonstrating that most patients who carry this mutation do so on a shared ancestral haplotype [11,12].…”
supporting
confidence: 85%
“…Conversely, PDB is rare in Scandinavia, the Indian subcontinent, China, Japan, and other countries in the Far East [9]. These observations are consistent with recent archeological studies that have indicated that PDB most probably originated in Britain and spread to other parts of the world as the result of migration and genetic admixture [10]. Genetic studies in patients with the P392L mutation of SQSTM1 (the most common causal mutation of PDB, see later) also support this hypothesis in demonstrating that most patients who carry this mutation do so on a shared ancestral haplotype [11,12].…”
supporting
confidence: 85%
“…Subsequently investigators have highlighted that the same mutation is often present on a conserved haplotype, which is consistent with a stable genetic change occurred in the affected population (16). This observation of a founder effect perfectly matches the epidemiology of Paget's disease (17), but only in the case of the SQSTM1 mutation. In Europe, Australia, and the United States, comparable rates of SQSTM1 mutation have been reported in or around the ubiquitin-associated domain.…”
mentioning
confidence: 65%
“…Archeological studies of skeletal remains suggest that these differences in prevalence could be consistent with PDB having arisen as the result of genetic mutations that predispose to the disease in people from North-West Europe many centuries ago, with spread to other regions of the world through emigration. (4) At a cellular level, PDB is characterized by increased numbers and activity of osteoclasts coupled with an increase in osteoblast activity. (5) Bone formation is increased but disorganized, with formation of woven bone, which is mechanically weak and subject to deformity and fracture.…”
Section: Introductionmentioning
confidence: 99%